2009
DOI: 10.1371/journal.pone.0006756
|View full text |Cite
|
Sign up to set email alerts
|

Stage Dependent Aberrant Regulation of Cytokine-STAT Signaling in Murine Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a complex autoimmune disease of unknown etiology that involves multiple interacting cell types driven by numerous cytokines and autoimmune epitopes. Although the initiating events leading to SLE pathology are not understood, there is a growing realization that dysregulated cytokine action on immune cells plays an important role in promoting the inflammatory autoimmune state. We applied phospho-specific flow cytometry to characterize the extent to which regulation of cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 51 publications
4
26
0
1
Order By: Relevance
“…Conflicting data exist regarding Stat5 in SLE (21,22). Although attenuated IL-2 expression in SLE T cells suggests reduced Stat5 activation (23)(24)(25), one study demonstrated increased Stat5 phosphorylation in SLE (22).…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting data exist regarding Stat5 in SLE (21,22). Although attenuated IL-2 expression in SLE T cells suggests reduced Stat5 activation (23)(24)(25), one study demonstrated increased Stat5 phosphorylation in SLE (22).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has demonstrated the ability to use correlational data obtained by phospho-specific flow cytometry to build directional, statistical maps of phospho-signaling networks within primary cells [8]. Although not yet utilized in any studies of T1D, the technique has been utilized in studies of an animal model of systemic lupus erythematosus (SLE) [9 • ]. SLE is a complex autoimmune disease of unknown cause that involves multiple interacting cell types driven by numerous cytokines and autoantigens.…”
Section: Phosphoepitope Flow Cytometrymentioning
confidence: 99%
“…Investigators in Dr Nolan’s laboratory applied phospho-specific flow cytometry to characterize the extent to which regulation of cytokine signal transduction through the STAT family of transcription factors was disturbed during the progression of SLE. Using a panel of 10 cytokines thought to have causal roles in the disease, they measured signaling responses at the singlecell level in five immune cell types from the MRLlpr mice [9 • ]. Their results suggested that negative feedback regulation opposed inflammatory cytokines that have self-sustaining activities, and suggested to them that a cytokine-driven oscillator circuit may drive the periodic disease activity observed in many SLE patients.…”
Section: Phosphoepitope Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations